Teacher Creativity in Using Mathematics Learning Media in Higher Grades in the Independent Curriculum at SDN 21 Rejang Lebong - Lastari, Nova (Journal of Primary Education, 2025)
This study aims to describe the creativity of mathematics teachers in using learning media in higher classes in the independent curriculum at SDN 21 Rejang Lebong and to describe the supporting and inhibiting factors of teacher creativity in using mathematics learning media in higher classes in the independent curriculum at SDN 21 Rejang Lebong. This study uses a qualitative research method, in which there are 4 steps in its implementation, namely: 1) observation, 2) documentation, 3) interviews, and 4) drawing conclusions. Based on these research steps, it can be concluded that teachers at SDN 21 Rejang Lebong meet the criteria for creative teachers, namely being able to produce new innovations in learning activities, teachers are able to create graphic media in mathematics learning, teachers can also create fun learning, teachers can also include students in all learning activities. In addition, there are supporting factors for teacher creativity in using mathematics learning media in the independent curriculum, namely: 1) the existence of a Learning Community (Kombel), 2) colleagues, 3) teaching tools from the Ministry of Education and Culture, and 4) the independent learning platform. Meanwhile, the inhibiting factors for teacher creativity in using mathematics learning media in the independent curriculum are: 1) student character, 2) student thinking ability level, 3) facilities and infrastructure, 4) costs, 5) how to make graphic media, and 6) limited time.